Guyana : Poverty Reduction Strategy Paper Progress Report 2004. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews Guyana's Poverty Reduction Strategy Paper (PRSP) Progress Report 2004. In spite of many challenges, the government made progress in implementing its Poverty Reduction Program. In particular, it pursued prudent macroeconomic policies, which improved economic fundamentals and created the framework for sustainable growth. Priority attention was also given to implementing reforms to improve the institutional and regulatory frameworks, public accountability, confidence building in the judicial and political systems, local government reforms, and the protection of fundamental human rights.